A Study of Citations to Wikipedia in Scholarly Publications. Issue 3 (2nd July 2016) - Tomaszewski, Robert; MacDonald, Karen I.
ABSTRACT: The debate on using Wikipedia as a credible academic information resource is dynamic and controversial. This study used the Web of Science (WoS) database and its "Cited Reference" and "Analyze Results" tools to identify and examine trends in the use of Wikipedia citations in scholarly, peer-reviewed publications for the years from 2002 to 2015. Results indicate that the use of Wikipedia citations in peer-reviewed journals has been increasing since 2002. Given that Wikipedia is considered a nonauthoritative source, it might be assumed that this resource is frequently being cited in open access (OA) journals, which are sometimes considered less rigorous when it comes to publication standards. Alternatively, it might be assumed that Wikipedia is being used by scholars from lesser-quality institutions or from developing countries, where access to authoritative information resources might be limited. This study examines these assumptions and describes the disciplines, research fields, and types of journals that are accepting Wikipedia as an authoritative reference source, thereby increasing its credibility. This research is intended to fuel informed debate on the issue, which will contribute to improvement in scholarly communication.